Integrating microalgae-based wastewater treatment, biostimulant production, and hydroponic cultivation: a sustainable approach to water management and crop production - Morillas-España, Ainoa; Pérez-Crespo, Raúl; Villaró-Cos, Silvia; Rodríguez-Chikri, Laura; Lafarga, Tomas (Frontiers in Bioengineering and Biotechnology, 2024)
A natural appearing microalgae-bacteria consortium was used to process urban wastewater. The process was done in an 80 m2 raceway reactor and the results were compared to an identical reactor operated using freshwater supplemented with commercial fertilisers. The biomass harvesting was done using commercial ultrafiltration membranes to reduce the volume of culture centrifuged. The membrane allowed achieving a biomass concentration of ∼9–10 g L−1. The process proposed avoids the use of centrifuges and the drying of the biomass, two of the most energy consuming steps of conventional processes. The specific growth rate in freshwater and the wastewater-based media was estimated as 0.30 ± 0.05 and 0.24 ± 0.02 days−1, respectively (p < 0.05). The maximum concentration reached at the end of the batch phase was 0.96 ± 0.03 and 0.83 ± 0.07 g L−1 when the biomass was produced using freshwater and wastewater, respectively (p < 0.05). The total nitrogen removal capacity of the system was on average 1.35 g m−2·day−1; nitrogen assimilation into biomass represented 60%–95% of this value. Furthermore, the P-PO43− removal capacity of the system varied from 0.15 to 0.68 g m−2·day−1. The outlet effluent of the reactor was used as a nutrient source in the hydroponic production of zucchini seedlings, leading to an increase in the root dry weight and the stem diameter compared to the water alone. The produced biomass showed potential for use as feedstock to produce plant biostimulants with positive effects on root development and chlorophyll retention.